Carmi Syndrome in a Preterm Neonate: A Multidisciplinary Approach and Ethical Challenge - Timothy D. Hicks; Himanshu Singh; Michel Mikhael; Anita R. Shah (Case Reports in Pediatrics)
Epidermolysis bullosa (EB) is characterized by blistering of the skin and mucosal erosions caused by hemidesmosomal abnormalities. EB is divided into 3 major subgroups depending on the particular location of tissue separation: EB simplex, dystrophic EB, and junctional EB. Junctional EB (JEB) can further be broken down into Herlitz, non-Herlitz, and JEB with pyloric atresia (Carmi syndrome) depending on genetic and histologic testing. When extensive, management of a patient with EB can be challenging due to not only cutaneous but also extracutaneous manifestations as well. Families and health care teams are often faced with difficult decisions in their infant’s best interest. We report a case of a preterm neonate with Carmi syndrome and unique findings on immunofluorescence studies. The patient’s course was complicated by multisystem involvement and ultimately death. A multidisciplinary approach was crucial in the light of diagnostic, therapeutic, and ethical challenges.